Adherence to the Porto Criteria Based on the Hungarian Nationwide Pediatric Inflammatory Bowel Disease Registry (HUPIR) - Müller, Katalin E.; Dezsőfi, Antal; Cseh, Áron; Szűcs, Dániel; Vass, Noémi; Nemes, Éva; Kadenczki, Orsolya; Tárnok, András; Szakos, Erzsébet; Guthy, Ildikó; Kovács, Márta; Karoliny, Anna; et al. (Frontiers in Pediatrics, 2021)
Objectives: According to the Porto criteria, upper endoscopy and ileocolonoscopy with histology for patients with pediatric inflammatory bowel disease (pIBD) are recommended with small bowel imaging (SBI). We aimed to evaluate the adherence to the Porto criteria and biopsy sampling practice and to evaluate the diagnostic yield of magnetic resonance enterography (MRE) first time in a nationwide pIBD inception cohort. Methods: Newly diagnosed pIBD cases (ages 0–18 years) are registered in the prospective, nationwide Hungarian Paediatric IBD Registry (HUPIR). We analyzed the diagnostic workup of patients recorded between the 1st of January 2007 and the 31st of December 2016. Results: Data for diagnostic workup was available in 1,523 cases. Forty percent of the cases had complied with the Porto criteria. Adherence to the Porto criteria increased significantly from 20 to 57% (p < 0.0001) between 2007 and 2016. The most frequent reason for the incomplete diagnostic work-up was the lack of small bowel imaging (59%). In 2007, 8% of cases had a biopsy from all segments, and this rate reached 51% by 2016 (p < 0.0001). We analyzed the diagnostic yield of MRE in 113 patients (10.1%), who did not have any characteristic lesion for Crohn's disease. The MRE was positive for the small bowel in 44 cases (39%). Conclusions: Adherence to the Porto criteria increased significantly during the 10-year period. This is the first study that reports multiple biopsy sampling as the less accepted recommendation. The diagnostic yield of MRE in patients without characteristic lesion for Crohn's disease is 39%.